2006
DOI: 10.1007/bf02974280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glutathione conjugates of 2,3-dibromopropene in male ICR mice

Abstract: Hepatotoxic potential of 2, 3-dibromopropene (2, 3-DBPE) and its conjugation with glutathione (GSH) were investigated in male ICR mice. Treatment of mice with 20, 50, and 100 mg/kg of 2, 3-DBPE for 24 h caused elevation of serum alanine aminotransferase and aspartate aminotransferase activities. The hepatic content of GSH was not changed by 2, 3-DBPE. Meanwhile, the GSH content was slightly reduced when mice were treated with 2, 3-DBPE for 6 h and significantly increased 12 h after the treatment. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The time-course study showed that depletion of GSH by production of S-bromopropyl GSH conjugate was parallel with hepatotoxicity induced by 1,3-DBP. In fact, the decreased level of hepatic GSH following treatment with 1-BP and 2,3-DBPE was also associated with increased hepatotoxicity in male ICR mice (Lee et al, 2005b;2006).…”
Section: S-mentioning
confidence: 91%
“…The time-course study showed that depletion of GSH by production of S-bromopropyl GSH conjugate was parallel with hepatotoxicity induced by 1,3-DBP. In fact, the decreased level of hepatic GSH following treatment with 1-BP and 2,3-DBPE was also associated with increased hepatotoxicity in male ICR mice (Lee et al, 2005b;2006).…”
Section: S-mentioning
confidence: 91%
“…: +82-53-810-2819; Fax: +82-53-810-4654; E-mail: taecheon@yumail.ac.kr tathione (GSH). [3][4][5][6][7] Some haloalkanes capable of forming GSH conjugates may cause toxicity related directly or possibly with GSH conjugation. For example, mice treated orally with 1-BP exhibit hepatotoxicity and immunotoxicity following depletion of GSH in liver and spleen.…”
Section: Introductionmentioning
confidence: 99%